Investigating Consumers’ Willingness to Pay for Eco-Friendly Products in Nigeria - Philip, Lydia Nkechi (International Journal Administration, Business & Organization, 2024)
The increasing concern for environmental conservation has enhanced the need for more environmentally friendly products throughout the globe thus affecting even the developing nations like Nigeria. The present research focuses on the examination of the extent of the premium that Nigerian consumers are willing to pay for green products, an area that lacks sufficient empirical evidence. Thus, the research aims of the study are to establish the level of this willingness, examine the factors influencing this willingness, and evaluate the consequences for business and sustainability. A combination of questionnaires and interviews as research tools for data collection was adopted. The study shows that most of the Nigerian consumers are willing to make premium prices to purchase environmentally friendly products, the main reason is quality and health. The findings agree with the literature that there is a need for better availability and information about green products to build consumer confidence and improve utilization, which could be helpful for organizations and government officials who seek to drive sustainable consumption in Nigeria.